At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To construct a polynomial [tex]\( P(x) \)[/tex] of degree 3 with the given properties, let's follow these steps:
1. Identify the roots and their multiplicities:
- There is a root of multiplicity 2 at [tex]\( x = 4 \)[/tex]. This means [tex]\((x - 4)^2\)[/tex] is a factor of the polynomial.
- There is a root of multiplicity 1 at [tex]\( x = -3 \)[/tex]. This means [tex]\((x + 3)\)[/tex] is a factor of the polynomial.
2. Form the polynomial with these factors:
Using the roots and their multiplicities, the polynomial can be initially written as:
[tex]\[ P(x) = C \cdot (x - 4)^2 \cdot (x + 3) \][/tex]
where [tex]\( C \)[/tex] is a constant coefficient that we need to determine.
3. Determine the constant [tex]\( C \)[/tex] using the y-intercept:
The y-intercept is given as [tex]\((0, -14.4)\)[/tex], which means [tex]\( P(0) = -14.4 \)[/tex]. Plugging [tex]\( x = 0 \)[/tex] into the polynomial will help us find [tex]\( C \)[/tex]:
[tex]\[ P(0) = C \cdot (0 - 4)^2 \cdot (0 + 3) \][/tex]
Simplify the expression:
[tex]\[ P(0) = C \cdot 16 \cdot 3 = 48C \][/tex]
Given that [tex]\( P(0) = -14.4 \)[/tex], we can set up the equation:
[tex]\[ 48C = -14.4 \][/tex]
4. Solve for [tex]\( C \)[/tex]:
[tex]\[ C = \frac{-14.4}{48} = -0.3 \][/tex]
5. Write the final polynomial:
Substituting [tex]\( C = -0.3 \)[/tex] back into the polynomial:
[tex]\[ P(x) = -0.3 \cdot (x - 4)^2 \cdot (x + 3) \][/tex]
Thus, the polynomial [tex]\( P(x) \)[/tex] is:
[tex]\[ P(x) = -0.3 (x - 4)^2 (x + 3) \][/tex]
1. Identify the roots and their multiplicities:
- There is a root of multiplicity 2 at [tex]\( x = 4 \)[/tex]. This means [tex]\((x - 4)^2\)[/tex] is a factor of the polynomial.
- There is a root of multiplicity 1 at [tex]\( x = -3 \)[/tex]. This means [tex]\((x + 3)\)[/tex] is a factor of the polynomial.
2. Form the polynomial with these factors:
Using the roots and their multiplicities, the polynomial can be initially written as:
[tex]\[ P(x) = C \cdot (x - 4)^2 \cdot (x + 3) \][/tex]
where [tex]\( C \)[/tex] is a constant coefficient that we need to determine.
3. Determine the constant [tex]\( C \)[/tex] using the y-intercept:
The y-intercept is given as [tex]\((0, -14.4)\)[/tex], which means [tex]\( P(0) = -14.4 \)[/tex]. Plugging [tex]\( x = 0 \)[/tex] into the polynomial will help us find [tex]\( C \)[/tex]:
[tex]\[ P(0) = C \cdot (0 - 4)^2 \cdot (0 + 3) \][/tex]
Simplify the expression:
[tex]\[ P(0) = C \cdot 16 \cdot 3 = 48C \][/tex]
Given that [tex]\( P(0) = -14.4 \)[/tex], we can set up the equation:
[tex]\[ 48C = -14.4 \][/tex]
4. Solve for [tex]\( C \)[/tex]:
[tex]\[ C = \frac{-14.4}{48} = -0.3 \][/tex]
5. Write the final polynomial:
Substituting [tex]\( C = -0.3 \)[/tex] back into the polynomial:
[tex]\[ P(x) = -0.3 \cdot (x - 4)^2 \cdot (x + 3) \][/tex]
Thus, the polynomial [tex]\( P(x) \)[/tex] is:
[tex]\[ P(x) = -0.3 (x - 4)^2 (x + 3) \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.